If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 7 = 8x + -12 Reorder the terms: 7 + 9x = 8x + -12 Reorder the terms: 7 + 9x = -12 + 8x Solving 7 + 9x = -12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 7 + 9x + -8x = -12 + 8x + -8x Combine like terms: 9x + -8x = 1x 7 + 1x = -12 + 8x + -8x Combine like terms: 8x + -8x = 0 7 + 1x = -12 + 0 7 + 1x = -12 Add '-7' to each side of the equation. 7 + -7 + 1x = -12 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = -12 + -7 1x = -12 + -7 Combine like terms: -12 + -7 = -19 1x = -19 Divide each side by '1'. x = -19 Simplifying x = -19
| 5z/6-7z/12=6 | | 5(3x-5)+2(3x+2)= | | 51+38=x | | 5z/6-7z/12 | | r(x)=3 | | 3x^2-5x-1=o | | 5-37=108 | | 4c-17=1/3(8-2c) | | 27/3=x | | 1/4(16f-4)= | | 90+90+143+x=360 | | 31-4= | | 90+90+143+x=180 | | 25-5z=15 | | e+4*2=14 | | 1/4(16f-4) | | x-23=k | | -2(7x-8)+5=14x+21 | | 80=4f+12 | | 4z/7-1=-7 | | -11=-5+3c | | 5=m/4-1 | | -4x-5y=-8 | | m=n+16 | | T=4s+3.67 | | 3j^2-26j+16=0 | | 2cos(3x)*cos(x)=-2 | | 3(1)-y=2(1)+y-1 | | x/8-7=9 | | 4xy-x^2+6x=0 | | 3x+2=8x+2 | | 8(t+2)=72 |